PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN PADA GAPENSI JABAR - Febriansyah, Angky (Jurnal Riset Akuntansi, 2018)
The employee performance is one of the successful company factors. Many ways that companies  have to continuously improve the employees performance, for example, for increasing the accounting information system. Therefore increasing the accounting information system are expected to improve the employees performance. The aim of this study was to determine the influence of accounting information system on the performance of employees at Gapensi Jabar. The method used in this study is descriptive and verificative methods. Descriptive method is used to describe the accounting information system on employee performance variables. While verification is used to determine the influence accounting information system on employee performance. For testing the research hypothesis using test Simple Linear Regression by using SPSS 23 software. The results of this study  shows that the accounting information system have a significant effect in improving the employees performance at  Gapensi Jabar.  Key Words : Accounting Information System and Employee performance